Absence of population asymmetry in the American Quarter Horse (Equus ferus caballus) performing skilled left and right manoeuvres in reining competition - Whishaw, Ian Q. (Laterality (Hove), 2015)
Use of the right hand by humans for speech-related hand gestures, writing and throwing exemplifies motoric asymmetry. There are reports of asymmetry in many other animal species, including reports of left preference in emotional responsivity, spontaneous behaviour and the trained performance of the horse, Equus ferus caballus. The present study used the novel approach of using judges' scores to examine asymmetry in an equestrian event. The study analysed the scores of five judges evaluating the reining performance of 482, three-year-old American Quarter Horses competing in a major competition. Reining requires that the horses perform the manoeuvres of spin, circle and stop directed to either the left or right and symmetrical performance is featured in the judging criteria. The scores were sensitive to performance level, sex and manoeuvre, but there was no evidence of a population asymmetry in the left vs. right direction of the manoeuvres. The results are discussed in relation to need of using a large number of subjects in measuring asymmetry, the expression of individual vs. population asymmetry as a function of morphological and behavioural measures, and the influence of behavioural training on asymmetry.